2019
DOI: 10.1177/1178622119861089
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Pollutants in the Water of Midland and Odessa, Permian Basin, West Texas

Abstract: The objective of this study is to evaluate the public water contamination in the cities of Midland and Odessa, West Texas. Even though both cities are geographically close, their sources of water for public use are different. For this study, the copper-, lead-, arsenic-, nitrate-, and chromium-level reports in drinking water, provided by the cities from 2008 to 2017, were organized and analyzed using Cubic Hermite Interpolation. The results for each contamination per city were compared and contrasted with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 32 publications
0
28
1
Order By: Relevance
“…Numerous studies have been conducted to identify the effect of oil and gas production on environmental changes. Unconventional oil and gas production provides a decreasing trend of groundwater quality (chloride, nitrate) over time in the Permian Basin, West Texas [5,6]. The land-use changes in West and Central Texas during the shale boom of 2008-2012 are a direct result from the utilization for unconventional reservoirs and the development of energy resources and other human contributing activities [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted to identify the effect of oil and gas production on environmental changes. Unconventional oil and gas production provides a decreasing trend of groundwater quality (chloride, nitrate) over time in the Permian Basin, West Texas [5,6]. The land-use changes in West and Central Texas during the shale boom of 2008-2012 are a direct result from the utilization for unconventional reservoirs and the development of energy resources and other human contributing activities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The land-use changes in West and Central Texas during the shale boom of 2008-2012 are a direct result from the utilization for unconventional reservoirs and the development of energy resources and other human contributing activities [7,8]. Previous studies [5][6][7][8] have suggested that oil and gas development affected various entities, including groundwater quality and land-use changes. However, few studies have combined both groundwater and land-use factors to identify how oil and gas development related to the environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained data of element contents in the soil of Shelekhov are confirmed by the work of other researchers in Russia 5,7,26,27 and in other regions of the world. 10,[32][33][34] The soil cover survey shows the presence of contaminating chemical elements in its composition, which might result in their accumulation in the adjacent areas, in the composition of agricultural crops, biological substrate, that of the human one inclusive as noted by other researchers. 34,56,57 The minimum and maximum contents of some toxic elements in soils around aluminum and anode plants being built close to Tayshet town are markedly similar to those of Shelekhov (Table 1).…”
Section: Cities With Aluminum Production In the Irkutsk Regionmentioning
confidence: 99%
“…At present, soils are factually a complicated natural-anthropogenic system due to the long-term inflow of toxicants caused by industrial production. [2][3][4][5][6][7][8][9][10] Aluminum production has been continuously growing worldwide because this element is actually irreplaceable in diverse industries. 11 Aluminum is derived from a rock with a complex composition-bauxite.…”
Section: Introductionmentioning
confidence: 99%
“…Organic additives include petroleum products and compounds altered or man-made [ 4 ]. Inorganic additives consist of alkaline earth and metal salts employed to alter properties of bentonite clay [ 5 , 6 , 7 ]. Soil properties and plant growth can be negatively affected from by the contents of drilling fluid wastes.…”
Section: Introductionmentioning
confidence: 99%